Repetitive enhancement of serum BDNF subsequent to continuation ECT. (11th September 2019) - Vanicek, T.; Kranz, G. S.; Vyssoki, B.; Komorowski, A.; Fugger, G.; Höflich, A.; Micskei, Z.; Milovic, S.; Lanzenberger, R.; Eckert, A.; Kasper, S.; Frey, R.
Abstract : Introduction: Continuation electroconvulsive therapy (c‐ECT) is highly effective for the prevention of depressive symptom relapse. There is a lack of understanding, about how c‐ECT works in humans, particularly with regard to its effects on brain derived neurotrophic factor (BDNF) concentrations. Here, we aimed to close a gap in the literature by evaluating BDNF levels in patients receiving c‐ECT. Methods: We included 13 patients with either unipolar or bipolar depression (mean age ± SD: 55.5 ± 17.1; f/m: 10/3; unipolar/bipolar: 10/3) who received between one and four c‐ECT (average per patient: 2.8). Serum BDNF (sBDNF) levels were assessed before and after each c‐ECT sessions. Clinical assessments were also administered both before and after treatment. Results: Our analysis revealed a significant increase in sBDNF after each treatment (c‐ECT 1‐3: P  < 0.001, c‐ECT 4: P  = 0.018). The application of multiple c‐ECT treatments was not, however, associated with further sBDNF enhancements. Psychometric scores were not significantly altered following c‐ECT. Discussion: An increase in sBDNF concentrations subsequent to c‐ECT parallel data from the animal literature, which has linked regularly applied electrical stimulation to neuroplastic processes. This finding suggests a relationship between ECT‐induced sBDNF concentrations and (sustained) remission status, considering a stable clinical condition across c‐ECT.